2007
DOI: 10.1002/eji.200636728
|View full text |Cite
|
Sign up to set email alerts
|

The B lineage potential of thymus settling progenitors is critically dependent on mouse age

Abstract: The nature and lineage potential, particularly that for B cells, of thymus settling progenitors (TSP) in the adult mouse has been the subject of considerable debate. Lack of B cell potential would suggest pre-thymic, whereas its presence would suggest intrathymic loss of B cell potential. Using limiting dilution analysis (LDA) in vitro and transfer experiments in vivo, we show that the B cell potential of TSP is critically dependent on mouse age, reaching a maximum of about 1 in 20 cells at birth, decreasing 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…It is important to note that our conclusions apply only to adult mice. The frequency of ETPs with B-lineage potential is increased in neonatal mice, 13,45 and ETPs may be a more significant source of thymic B cells in early life.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that our conclusions apply only to adult mice. The frequency of ETPs with B-lineage potential is increased in neonatal mice, 13,45 and ETPs may be a more significant source of thymic B cells in early life.…”
Section: Discussionmentioning
confidence: 98%
“…However, these T-B potent ETPs are estimated to be a very small fraction of the ETP population (Porritt et al, 2004;Balciunaite et al, 2005;Lu et al, 2005;Sambandam et al, 2005;Ceredig et al, 2007). A key prediction of this model, therefore, is that thymus-settling ELPs undergo extensive cell division, generating large numbers of downstream ETPs.…”
Section: Is the Thymus Colonized By Lymphoid-specified Progenitors Wimentioning
confidence: 96%
“…Progenitor populations defined as DN1 Kit hi , or as ETP, are themselves heterogeneous, and subsets have been described with CD24 (Porritt et al, 2004), Flt3 (CD135) (Sambandam et al, 2005), and CCR9-EGFP expression in CCR9 reporter mice (Benz and Bleul, 2005;Heinzel et al, 2007). The rare ETP subset defined by expression of Flt3, and also by expression of high levels of EGFP in CCR9 reporter mice, contains some B lineage potential (Benz and Bleul, 2005;Sambandam et al, 2005;Ceredig et al, 2007;Heinzel et al, 2007). For some ETPs, T and B potential have been demonstrated in the same cell (Benz and Bleul, 2005;Heinzel et al, 2007).…”
Section: Progenitors In Thymusmentioning
confidence: 98%
“…It is generally believed that the so-called thymic seeding precursor (TSP) still has the capability of generating B cells, NK cells, DCs and other myeloid cells [2,5,6,10,11]. Upon receiving the Notch signal, the differentiation potential towards the B-cell lineage of the TSP is rapidly lost [2,10,11], whereas other lineage options are still maintained [2,5,6,10,11]. However, a recent study using an IL-7Ra reporter mouse indicated that the non-T-cell lineage differentiation of these progenitors is not, or only very rarely, occurring under physiologic conditions [12,13].…”
Section: Introductionmentioning
confidence: 99%